Prevalence and Severity of Carpal Tunnel Syndrome in Women - P Yazdanpanah; S Aramesh; A Mousavizadeh; P Ghaffari; Z Khosravi (Tehran University of Medical Sciences, 2012)
Background: Carpal tunnel syndrome (CTS) is entrapment of median nerve in carpal tunnel of the wrist. The prevalence of CTS related to pregnancy and non-pregnancy is unknown in some countries such as Iran. The main aim of this study was to determine the prevalence of CTS in women of Boyerahmad Township located in South-West part of Iran. Methods: This cross-sectional descriptive analytic study was done since February 2010 to January 2011 in Obstetrics and Gynecology clinics in 2656 non-pregnant and 1508 pregnant women. The women that had clinical symptoms of CTS performed standard electro diagnostic techniques for rule in or rule out of CTS. Results: The prevalence of CTS in pregnant and non- pregnant women was 3.4and    2 .3 percent respectively. The prevalence of CTS in all women was 2.7%. Overall, 51 pregnant women had CTS that 59.4% had mild, 18.8 % had moderate and 21.9% had severe CTS. Sixty-one non-pregnant women had CTS that 73.6 %had mild, 20.8 %t had moderate and 5.6 % had severe CTS. Conclusion: Although the prevalence of CTS in Iranian pregnancy is higher than non-pregnancy women conservative treatment is safe and more effective.